MENELISIK PESAN MORAL DI BALIK POLIGAMI (Deskripsi Historis Kehidupan Muhammad SAW. dan Implikasinya dalam Islam) - Ambar, Iriani (LPPM IAIN Parepare, 2015)
Polygamy is a controversial issue up to now. Many argued ideas are explored both by those who oppose to it and those agree with it. The arguments usually center around the advantages and disadvantages of polygamy. Some practices of polygamy provoke conflicts in family. Yet, it cannot be denied that some other practices remain place families in harmonious life. Therefore, it must be well comprehended how polygamy should be practiced.